Burst Laser-Driven Plasmonic Photochemical Nanolithography of Silicon with Active Structural Modulation - Liping Shi; Ji Yan; Shuyao Zhang; Panpan Niu; Jiao Geng; Günter Steinmeyer (Ultrafast Science)
Femtosecond laser ablation-driven periodic surface structuring offers a promising method for large-scale and high-throughput nanolithography technique. However, the self-organized periodic structures typically manifest constraints in terms of tunable period and depth, as well as suboptimal regularity, which restricts their broader application potential. Here, in terms of a rarely explored laser-induced photochemical mechanism for nonablative structuring, we demonstrate manufacturing of sub-wavelength oxidative grating structures on silicon films with active structural modulation. In this scenario, the plasmonic field plays a pivotal role in dragging oxygen ions from surface into the silicon, greatly speeding up oxidation rates. While high oxygen doping levels can already be achieved with single-pulse exposure, far superior results are obtained with the application of 40-MHz burst mode pulse trains, mitigating the formation of excessively large nanocrystallites. Furthermore, it is revealed that the periodicity and modulation depth of laser-writing nanograting are both dependent on the number of pulse per burst. This offers a convenient scheme for actively controlling laser plasmonic lithography.